Milk, Yogurt, and Cheese Intake Is Positively Associated With Cognitive Executive Functions in Older Adults of the Canadian Longitudinal Study on Aging. (11th June 2021) - Tessier, Anne-Julie; Presse, Nancy; Rahme, Elham; Ferland, Guylaine; Bherer, Louis; Chevalier, Stéphanie
Abstract: Background: Dairy products provide essential nutrients such as calcium and vitamins B12 and D, and include bioactive peptides and fermented products, which may be beneficial for cognition, especially in older adults. Yet, few studies of large contemporary cohorts have investigated this relationship using sensitive domain-specific cognitive tests. Method: In community-dwelling older adults of the Canadian Longitudinal Study on Aging (2011–2015), we examined cross-sectional associations between total and specific dairy product intake and performance in 3 cognitive domains (executive functions, memory, and psychomotor speed). Cheese, milk, yogurt, regular-fat, low-fat, and fermented dairy product intake frequencies were estimated using a food frequency questionnaire; participants were classified into quartiles. Multivariate analyses of covariance models were applied to estimate differences. Results: In 7 945 participants (65–86 years, 49% women, 97% Caucasian), the mean dairy product intake was 1.9 (1.1) times/d. Total dairy product, cheese, and low-fat dairy product intakes were positively associated with the executive function domain and yogurt intake with the memory domain (all p < .05), independently of important covariates including age, gender, education, and diet quality. Intakes of total dairy product, cheese, and low-fat dairy product were associated with verbal fluency specifically (all p < .05). Participants with a dairy product intake >2.5 times/d had a higher score compared to those consuming less. No associations were found with psychomotor speed. Conclusions: This large cohort study suggests a specific role for dairy components in executive function phonemic verbal fluency and memory. Dairy product intake, a modifiable factor, may be targeted in cognitive health-promoting interventions.